Gemella morbillorum Endocarditis - Serap Ural; Sureyya Gul Yurtsever; Bahar Ormen; Nesrin Turker; Figen Kaptan; Sibel El; Zehra Ilke Akyildiz; Nejat Ali Coskun (Case Reports in Infectious Diseases)
Infective endocarditis caused by Gemella morbillorum is a rare disease. In this report 67-year-old male patient with G. morbillorum endocarditis was presented. The patient was hospitalized as he had a fever of unknown origin and in the two of the three sets of blood cultures taken at the first day of hospitalization G. morbillorum was identified. The transthoracic echogram revealed 14 × 10 mm vegetation on the aortic noncoronary cuspis. After 4 weeks of antibiotic therapy, the case was referred to the clinic of cardiovascular surgery for valve surgery.